Trading with charts for absolute return - Fischer, Robert 1941- (Wiley, 2011)
"How to use chart patterns to consistently achieve absolute returns. Robert Fischer, a pioneer in developing trading strategies for Fibonacci price and time analysis, has now developed charting analysis that achieve absolute returns in bull, bear, and trendless markets. In Trading with Charts for Absolute Returns, Fischer provides traders with a shortcut from the intensive programming and data analysis work, explaining which patterns work, the best markets to trade using the strategies, and advanced trading signals. Uncovers the key chart patterns that work best in combination to provide real returns year-after-year and in all markets. Provides an augmented futures strategy for bear markets. Includes exclusive access to the Trading with Charts for Absolute Returns Web site with historical data and trading signals. While relative returns provide a means of judging performance on a comparative basis, as the saying goes, "you can't eat relative returns." Absolute returns is the only thing that matters, and Trading with Charts for Absolute Returns shows how to routinely achieve just that"--Provided by publisher.
Print version record
Keywords: Stocks -- Charts, diagrams, etc; Stocks -- Charts, diagrams, etc -- Prices; Speculation; Actions (Titres de société); Prix; Tableaux, graphiques, etc; Spéculation; speculating; BUSINESS & ECONOMICS; Investments & Securities; General; Stocks; Stocks; Prices; Charts, diagrams, etc